Supersonic jet steam dry ultrafine crushing / grading / quartz modification integrated method
The quartz powder is crushed and modified by supersonic steam milling, which solves the problems of high energy consumption and complex modification in the prior art, realizes the efficient integrated preparation of quartz powder, improves dispersion and fluidity, and Reduced production costs.
Patent Information
- Application Number
- CN202310779572.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art has high energy consumption, large equipment wear and many impurities when preparing ultrafine quartz powder. The modification process of quartz powder is complex and costly, making it difficult to achieve the integration of crushing and modification.
The quartz is crushed and modified by supersonic steam milling method, and the steam prepared by boiler or factory waste heat is accelerated at high temperature and sprayed with silane coupling agent for modification, simplifying the process flow and improving energy utilization.
The ultra-fine crushing, grading and modification of quartz powder is achieved, which reduces energy consumption and equipment losses, improves the dispersion and flowability of output and finished products, and reduces impurities and production costs.
Smart Images

Figure CN119220111A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ultrafine powder preparation and powder surface modification, and particularly relates to an integrated method for ultrafine grinding / classification / modification of quartz by using a superheated steam dry grinding method. Background Art
[0002] Quartz is an important industrial mineral raw material with excellent physical and chemical properties. The ore body is hard, wear-resistant, and has stable chemical properties. It has a high Mohs hardness and is difficult to process and crush. High-purity ultrafine quartz powder is widely used in high-tech fields such as aerospace, semiconductors, integrated circuits, and optical fiber cables. my country has regarded it as a strategic resource. Quartz has a high Mohs hardness and is difficult to process and crush. Due to the hydrophilicity of the surface of quartz powder, it is difficult to be compatible with organic polymer materials. Therefore, it is necessary to modify the surface of ultrafine quartz powder to increase its dispersibility and fluidity.
[0003] As for the crushing, at present, my country often uses stirred mills, vibration mills, mechanical impact mills and air flow mills to produce ultrafine quartz powder. In the process of using traditional methods to prepare ultrafine quartz powder, not only is the energy consumption high, the equipment is worn out, but there are also many impurities. There are two main methods for modifying quartz powder: wet method and dry method. The wet process is more complicated and costly, and is rarely used in industrial production; the dry process does not require post-processing and has low cost. It is the main method for surface modification of mineral materials. The dry process is to first add the quartz powder to the modification equipment for preheating and drying, and add the modifier during the preheating process to make the silane coupling agent better chemically bond with the surface of the quartz powder, thereby completing the modification.
[0004] Using superheated steam kinetic mill to crush quartz can produce ultrafine quartz powder, which has low energy consumption and low production cost and can be mass-produced. The quartz powder is modified while being crushed by steam kinetic mill, and no preheating is required, which saves energy. The high-temperature resistant silane coupling agent is used to modify the quartz powder under high temperature conditions. Summary of the invention
[0005] The purpose of the present invention is to provide an integrated method for ultrafine grinding / classification / modification of quartz based on supersonic steam dry method. The quartz is ultrafinely ground by utilizing the strong grinding ability of the steam kinetic energy mill, and while grinding, a diluted silane coupling agent is added to the grinding chamber to modify the quartz. The ultrafine grinding / classification / modification of quartz is integrated, achieving the purpose of energy saving and convenience.
[0006] A method for integrating ultrafine grinding / classification / modification of quartz based on supersonic steam dry method, comprising the following steps: (1) using steam prepared by boiler or industrial waste heat as the steam source of superheated steam mill; (2) adding prepared silane coupling agent modification liquid into the grinding chamber while grinding the quartz.
[0007] The specific steps are as follows: the steam produced by the waste heat of the boiler or the factory is heated to 150 ~ 500 ℃ by the heater, and then accelerated to the supersonic state by the supersonic acceleration device. The quartz powder is accelerated by the airflow and rubbed and collided in the crushing chamber, thereby being crushed. While crushing, the prepared modifier is sprayed into the crushing chamber to fully mix the modifier with the quartz powder to complete the modification of the quartz powder. After the crushing is completed, the particle size requirement (D 50 The quartz powder with a particle size of 0.2 ~ 20 μm) passes through the classifier and enters the bag filter for collection under the action of the induced draft fan.
[0008] As a preferred embodiment of the present invention, the D of the quartz powder raw material to be crushed and modified 50 5μm ~ 1 mm.
[0009] As a preferred embodiment of the present invention, ultrafine quartz powder D after crushing / classification / modification 50 0.2 ~ 20 μm.
[0010] As a preferred embodiment of the present invention, the pressure of supersonic steam is 0.3-4.0 MPa and the temperature is 150-500°C.
[0011] As a preferred embodiment of the present invention, the temperature in the crushing chamber is about 150-500°C, which can meet the temperature required for quartz modification, avoids the preheating in the conventional quartz modification method, and improves energy utilization.
[0012] As a preferred embodiment of the present invention, the quartz modifier used is A-172 type silane coupling agent, and the ratio of the modifier is 20% silane coupling agent, 72% alcohol, and 8% water. The alcohol is generally ethanol (p-ethoxysilane) and methanol (p-methoxysilane).
[0013] As a preferred embodiment of the present invention, nitrogen is used for high temperature pulse, and the temperature is about 150-500°C.
[0014] As a preferred embodiment of the present invention, a variety of methods for adding modifiers are provided according to different actual situations, namely: fully mixing the modifier with the raw material before crushing; spraying the modifier into the modification chamber through an atomizing nozzle; adding the modifier through an atomizing nozzle at the outlet of the classifier.
[0015] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: (1) the integrated crushing / classification / modification process for preparing ultrafine quartz powder is achieved, which greatly simplifies the operation process.
[0016] (2) Use a steam kinetic energy mill to crush quartz. Supersonic superheated steam has strong crushing ability and less equipment loss during the crushing process, so there are fewer impurities in the finished product.
[0017] (3) The present invention can use factory waste heat to prepare steam, thereby improving energy utilization.
[0018] (4) A high-temperature resistant silane coupling agent is used in the modification process, which can meet the requirements of use in the high-temperature environment of the steam kinetic energy mill. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to explain the present invention more clearly, the present invention is briefly introduced in combination with a process flow chart and an example.
[0020] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0021] Embodiment 1: A method for integrating supersonic jet steam dry ultrafine grinding / classification / modification of quartz, comprising the following steps: The method for preparing modified ultrafine quartz powder by superheated steam kinetic energy grinding dry method of the present invention mainly consists of three parts: air source system, grinding and grading modification system, and collection system. It includes an air compressor, a boiler, a heater, a fluidized bed air flow mill, a feeder, a classifier, a bag filter, and an induced draft fan. Combining the above system, the preparation of ultrafine modified quartz powder by superheated steam kinetic energy grinding dry method specifically includes the following process: the steam prepared by the boiler passes through the heater and the supersonic acceleration device, enters the grinding chamber to grind the added quartz raw material, and adds the previously prepared A-172 type silane coupling agent (the ratio of the modifier is 20% silane coupling agent, 72% alcohol, and 8% water. Alcohol is generally ethanol or methanol) while grinding. In the environment of superheated steam, the modifier and quartz powder are fully mixed to complete the modification. After modification, the quartz that meets the particle size requirements passes through the classifier and enters the bag filter for collection under the action of the induced draft fan, and the quartz powder that does not meet the particle size requirements returns to the crushing chamber for further crushing and modification. The particle size test of the ultrafine quartz powder obtained by this method is carried out. 50 The particle size is 0.5 ~ 20 μm, and the specific surface area is 12840 ~ 20000 m 2 / kg, the output is 11.6 ~ 20 kg / h, the zero point of the modified ultrafine quartz is around pH=6.2; when pH<6.2, the Zeta potential is positive, and after pH>6.2, the Zeta potential is negative. When the amount of silane coupling agent A-172 is 0~0.48% during modification, its viscosity is 2800-~50mPa*s, and the surface properties of the modified quartz powder change from hydrophilic to hydrophobic, which improves the wettability of the quartz powder surface and increases the dispersibility of the quartz powder. And after modification, the quartz powder is graded, which is convenient for the collection of finished products. The use of this method greatly improves the efficiency of quartz crushing and modification, and also saves costs.
[0022] Example 2: A method for integrating supersonic jet steam dry ultrafine grinding / classification / modified quartz, comprising the following steps: using factory waste heat to prepare steam as a steam source, heating it to 150-500°C in a heater, and accelerating the steam to a supersonic state through a supersonic acceleration device. Add titanium dioxide raw material (D 50 5 μm ~ 1 mm), crushed under the action of supersonic superheated steam. After crushing, the material is classified by the classifier under the action of the induced draft fan, and the quartz powder that does not meet the particle size requirements will return to the crushing chamber for further crushing. The particle size after classification is D 50 About 0.3 ~ 10 μm. Before the material enters the dust collector pipeline, the pre-configured modifier (PT-02 powder modifier) is sprayed in an amount of 0.3 ~ 0.5% of the total powder to modify the powder and realize the integrated pulverization and modification of titanium dioxide. The modified titanium dioxide is used in white masterbatch, which significantly improves the hiding power and the light density value by 2.5 times compared with before treatment. The lipophilicity of titanium dioxide after treatment is significantly improved, and the balanced torque and maximum torque are reduced by nearly 2.45 N·m. A non-polar, cross-linkable silicone film layer is formed on the surface of titanium dioxide, which greatly improves the whiteness, dispersibility and glossiness of titanium dioxide and reduces the oil absorption.
[0023] Example 3: A method for supersonic jet steam dry ultrafine grinding / classification / modification of quartz, comprising the following steps: Example 3 is different from Example 2 in that the material to be ground is precipitated barium sulfate, the model of the powder modifier is AD8058, and the modifier is fully mixed with the raw material before grinding. 50 7.5 μm precipitated barium sulfate D 50The particle size of the precipitated barium sulfate treated with the modifier is 0.2 ~ 15 μm, and the output is 8 ~ 15 kg / h. The activity of the precipitated barium sulfate after being treated with the modifier is high, and the activity can reach 97.83% after modification. The hydrophobicity of the product is also greatly improved, the dispersibility is good, and it has good affinity with various resins. Compared with the traditional pulverization modification method, the ultrafine precipitated barium sulfate prepared by this method has less impurities, the material consistency can reach more than 99.5%, and there are no toxic and harmful substances, which can ensure the safety and cleanliness of the product. And the prepared product has a smaller particle size, which can meet more usage requirements. Modifying the material while pulverizing greatly simplifies the industrial process, reduces equipment investment and modification costs, and the modification effect is also better.
[0024] Embodiment 4: A method for integrating ultrafine grinding / classification / modification of quartz by supersonic jet steam dry method, comprising the following steps: Wollastonite with ultrafine aspect ratio is widely used as filler in the fields of plastics, fibers, rubber and other organic polymer materials, as well as paints, adhesives, etc. The integrated method of grinding and modification of the present invention can not only improve its compatibility with organic polymers and resins, but also improve the dispersibility of wollastonite powder, thereby greatly improving the added value of its products. Specifically, it includes the following process: adding wollastonite raw material with a particle size of 1 to 5 mm to the grinding chamber through a feeder, and the steam prepared by the boiler passes through an acceleration device and supersonic superheated steam generated by a supersonic nozzle. The material is driven by the airflow to rub and collide in the grinding chamber to complete the grinding. An atomizing nozzle is also provided in the grinding chamber, and the modifier is added to the grinding chamber through the atomizing nozzle to be fully mixed with the material to modify the wollastonite. Under the action of the induced draft fan, the material that meets the particle size passes through the classifier and enters the bag filter for collection. A spray nozzle is also installed at the outlet of the classifier to perform secondary modification on the wollastonite powder that has been crushed and modified, making the modification more complete. In this example, the modifier used is methacryloyloxypropyltrimethoxysilane coupling agent, which has a boiling point of 255°C and can meet the high temperature environment of modification. The wollastonite powder D prepared by this method 50 About 0.5~ 5 μm. In the steam environment, the aspect ratio of wollastonite powder is greatly improved. Generally, the aspect ratio of wollastonite is about 7:1~10:1. After ultra-fine grinding and modification, the aspect ratio of wollastonite powder can reach 20:1~30:1, and the added value of the product is also greatly improved, about 1000~1600 yuan / t.
[0025] The modifiers used in the present invention are all high temperature resistant silane coupling agents, which have low thermal weight loss in high temperature environments and can maintain good modification performance. They can not only meet the high temperature environment in the crushing chamber to complete the modification of the material, but also make the material modification more complete under high temperature (150 ~ 500 ℃) conditions, and high temperature accelerates the modification of the material, greatly improving the output, greatly simplifying the process flow in industry and saving production costs.
Claims
1. A dry ultrafine grinding / classification / modified quartz integrated method, characterized in that: The following steps are involved: While the quartz powder raw material is being crushed in the crushing chamber, it fully reacts with the added high temperature resistant modifier (such as silane coupling agent that can withstand temperatures of 500°C), thereby achieving the modification of ultrafine quartz powder while crushing. After the crushing and modification are completed, the quartz powder that meets the particle size requirements (0.2 ~ 20 μm) enters the bag filter for collection through the classifier, and the powder that does not meet the particle size requirements returns to the crushing chamber for further crushing + modification.
2. The method of integrating supersonic steam dry ultrafine grinding / classification / modified quartz according to claim 1, characterized in that: When using superheated steam to crush quartz, the process of using a high temperature resistant modifier (500°C) for modification often needs to be carried out under high temperature conditions. During the crushing process, the temperature in the crushing chamber can reach 150~500°C, which just meets the modification temperature of quartz powder. This avoids heating and saves energy.
3. The method of integrating supersonic steam dry ultrafine grinding / classification / modified quartz according to claim 1, characterized in that: The ultra-fine grinding of quartz is achieved, and D 50 Quartz powder with a diameter of 5 μm to 1 mm is crushed to D 50 0.2 ~ 20 μm.
4. The method of integrating supersonic steam dry ultrafine grinding / classification / modified quartz according to claim 1, characterized in that: Quartz powder raw materials that need to be crushed and modified 50 The particle size of the ultrafine quartz powder is 5 μm ~ 1 mm. The quartz powder is modified while being crushed. After crushing / classification / modification, the ultrafine quartz powder D50 is 0.2 ~ 20 μm. The zero-electric point of the modified ultrafine quartz is around pH = 6.
2. When pH < 6.2, the Zeta potential is positive, and when pH > 6.2, the Zeta potential is negative. The surface properties of the modified quartz powder change from hydrophilic to hydrophobic. When the amount of silane coupling agent A-172 is 0-0.48%, its viscosity is 2800-~50mPa*s, and the surface area is 12840 ~ 20000 m 2 / kg, which improves the wettability of the quartz powder surface and increases the dispersibility of the quartz powder. And after the modification, the quartz powder is graded, which is convenient for the collection of finished products.
5. The method of integrating supersonic steam dry ultrafine grinding / classification / modified quartz according to claim 1, characterized in that: The steam pressure used in the crushing process is 0.3 ~ 4.0 MPa, the temperature is 150 ~ 500 ℃, and the steam source is boiler or factory waste heat.
6. The method of integrating supersonic steam dry ultrafine grinding / classification / modified quartz according to claim 1, characterized in that: It is not only suitable for crystalline quartz and fused quartz, but also for other non-metallic minerals that need to be crushed and modified. For example, the D50 of titanium dioxide raw material is 5 μm ~ 1 mm, and the D50 after crushing and modification is about 0.3 ~ 10 μm. The modified titanium dioxide is used in white masterbatch, which significantly improves the hiding power and the light density value by 2.5 times compared with that before treatment. The lipophilicity of titanium dioxide after treatment is significantly improved, and the equilibrium torque and maximum torque are reduced by nearly 2.45 N·m. The D50 of barium sulfate raw material is 7.5 μm, and after crushing and modification, the D50 is 0.2 ~ 15 μm. After modification, the activity can reach 97.83%, and the hydrophobicity of the product is greatly improved.
7. The method of integrating supersonic steam dry ultrafine grinding / classification / modified quartz according to claim 1, characterized in that: When the modification temperature is too high, the modifier that is not resistant to high temperatures will be decomposed and carbonized, and the concentration of stable silanol in the solution will also decrease, resulting in a decrease in the bonding strength between the modifier and the particles. The modification effect of the modifier will be reduced. For example, when silane A174 is used to modify ultrafine sulfuric acid, the reaction temperature is 80°C and the product activation rate is 82.83%. As the temperature continues to rise, the product activation rate will gradually decrease, eventually leading to modification failure. The modifier used is the high-temperature resistant A-172 silane coupling agent, which can withstand temperatures of 150-500°C, avoiding the failure of the modifier caused by excessively high temperatures in the crushing chamber.
8. The method of integrating supersonic steam dry ultrafine grinding / classification / modified quartz according to claim 1, characterized in that: The modifier is added into the pulverizing chamber by supersonic continuous spraying or dripping (addition) method linked with the quartz powder feeding speed to ensure uniform mixing of the modifier and the quartz powder.
9. The method of integrating ultrafine grinding / classification / modified quartz based on supersonic steam dry method according to claim 1, characterized in that: The gas-solid flow filtration method after pulverization modification uses ceramic / sintered coating or titanium alloy as collector and filter material, which can withstand temperatures of 150-500℃ and composite high temperature (80-120℃ high temperature dry gas (dew point temperature -60 to -70℃)) pulse cleaning. When the amount of silane coupling agent A-172 is 0~0.48% during modification, its viscosity is 2800~50mPa*s, and its product viscosity is reduced. It can prevent the adhesion of the obtained ultrafine powder.